2017
DOI: 10.3928/19382359-20170316-01
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of the Health Effects of Electromagnetic Fields

Abstract: There has been an exponential increase in the use of electronic devices over the past few decades. This has led to increased exposure to electromagnetic fields (EMF). Electric fields result from differences in voltage, whereas magnetic fields result from the flow of electric current. Higher-frequency waves of EMF have more energy than lower-frequency waves, and thus generally tend to be more harmful. An EMF activates cellular stress response and also causes breaks in DNA strands. There are many methodological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 6 publications
0
12
0
3
Order By: Relevance
“…The biological mechanism via which radiofrequency radiation exposure increases the breast cancer risk may be associated with the fact that exposure to radiofrequency radiation has been revealed to result in mammary cell damage and ROS formation (40), which are the primary causes of DNA strand breaks that result in cell death (15,40,41). Although it has been indicated that non-ionizing radiation exhibits in sufficient energy to cause DNA strand breaks, the primary cause of DNA strand breaks is considered to be a by-product of ROS metabolism and not high-energy radiation (42)(43)(44). A number of in vitro studies have demonstrated an association between radiofrequency exposure and ROS production, resulting in DNA single-and double-strand breaks (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological mechanism via which radiofrequency radiation exposure increases the breast cancer risk may be associated with the fact that exposure to radiofrequency radiation has been revealed to result in mammary cell damage and ROS formation (40), which are the primary causes of DNA strand breaks that result in cell death (15,40,41). Although it has been indicated that non-ionizing radiation exhibits in sufficient energy to cause DNA strand breaks, the primary cause of DNA strand breaks is considered to be a by-product of ROS metabolism and not high-energy radiation (42)(43)(44). A number of in vitro studies have demonstrated an association between radiofrequency exposure and ROS production, resulting in DNA single-and double-strand breaks (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been indicated that non-ionizing radiation exhibits in sufficient energy to cause DNA strand breaks, the primary cause of DNA strand breaks is considered to be a by-product of ROS metabolism and not high-energy radiation (42)(43)(44). A number of in vitro studies have demonstrated an association between radiofrequency exposure and ROS production, resulting in DNA single-and double-strand breaks (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“… 7 11 In our study, we found that participants with a smartphone addiction had a significantly increased 1.43-fold risk of breast cancer compared to those without addiction. Our results suggest that people with smartphone addiction could have massive radiofrequency exposure compared to people without smartphone addiction, 36 , 37 therefore increasing their risk of developing breast cancer.…”
Section: Discussionmentioning
confidence: 80%
“…La IARC clasifica los campos electromagnéticos de radiofrecuencia como posibles carcinogénicos para los seres humanos, con un riesgo asociado a la exposición de campos magnéticos superiores a 0,4 m que duplica el riesgo de desarrollar leucemia; sin embargo, no hay evidencia suficiente de asociación entre la radiación no ionizante de baja frecuencia y un mayor riesgo de desarrollar tumores cerebrales en la población infantil y adolescente expuesta a campos electromagnéticos de radiofrecuencia de los teléfonos móviles (21) .…”
Section: Radiación Ionizanteunclassified